Defining the Problem of Choosing Extracurricular Activities for Children in Russia - Anita Poplavskaya; Ivan Gruzdev; Andrey Petlin (Вопросы образования, 2018)
The article provides an overview of international studies on parental involvement in extracurricular activities, which identify the major factors affecting the choice of such activities: family finances, cultural capital, parental education and habitus, local educational infrastructure, and the possibility of making informed choices. The empirical basis of the research was provided by the findings from semi-structured interviews with parents of Moscow preschool and school-aged children engaged in extracurricular activities conducted in spring 2017. The study also makes use of the quantitative data obtained by the 2017 Monitoring of Education Markets and Organizations. We analyze the frequency of using particular sources of information in choosing extracurricular classes, the criteria of parental choices and expectations, and the types of choice scenarios. The findings call into doubt the feasibility and potential benefits of a number of extracurricular activity initiatives envisaged by the national policy.